2017
DOI: 10.3747/co.24.3611
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Care Trajectory at a Canadian Centre: An Evaluation of How Wait Times Affect Clinical Outcomes

Abstract: Background Lung cancer continues to be one of the most common cancers in Canada, with approximately 28,400

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 33 publications
6
39
0
Order By: Relevance
“…A 2016 study showed that time-to-treatment (TTT) from first medical oncology visit was 34 days, improved to 22 days even after reflex testing of EGFR mutational analysis was implemented [ 13 ]. A study from Canada showed that median TTT from the diagnosis of lung cancer to the initiation of treatment was 32 days and that the patients whose treatment was not initiated within 30 days had significantly worse survival compared to the patients whose treatment was initiated within 30 days [ 14 ]. Estimating the incidence of EGFR mutation using existing clinical characteristics could be valuable in facilitating decision making as to whether systemic chemotherapy or TKI should be started while awaiting the result of EGFR mutation analysis, hence shortening the TTT, and improving patient outcome.…”
Section: Introductionmentioning
confidence: 99%
“…A 2016 study showed that time-to-treatment (TTT) from first medical oncology visit was 34 days, improved to 22 days even after reflex testing of EGFR mutational analysis was implemented [ 13 ]. A study from Canada showed that median TTT from the diagnosis of lung cancer to the initiation of treatment was 32 days and that the patients whose treatment was not initiated within 30 days had significantly worse survival compared to the patients whose treatment was initiated within 30 days [ 14 ]. Estimating the incidence of EGFR mutation using existing clinical characteristics could be valuable in facilitating decision making as to whether systemic chemotherapy or TKI should be started while awaiting the result of EGFR mutation analysis, hence shortening the TTT, and improving patient outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Looking at these studies some reached comparable results, like Coughlin et al, who showed that UICC stage II NSCLC patients have a significantly decreased survival when the patient work-up from the decision to operate to resection took two months or more 9 . Kasymjanova et al reached similar results, describing a beneficial effect on survival for early and locoregional stage disease, when the biopsy-to-treatment interval was 30 days or less 10 . In contrast to these results some publications state that there is no relationship between survival and prolonged delay to treatment or even that shorter delay causes reduced survival 11 , 12 .…”
Section: Discussionmentioning
confidence: 68%
“…Most cases (90%) were non-small cell lung cancer, 36% of the patients had no comorbid conditions, 28% were never smokers, and 60% were advanced stage. Characteristics of the study sample were similar to registry patient characteristics except for smoking status where the study sample had almost double the number of never smokers [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…We collected the following data from the registry: age at diagnosis, sex, referral source, referral date, diagnosis date, and stage of disease. Stages I and II were categorized as early, stage III as locoregional, and stage IV as advanced [ 14 ]. Additionally, postal codes were used to convert to an area-based deprivation score for each patient [ 15 ].…”
Section: Methodsmentioning
confidence: 99%